Plano de carreira do magistério público municipal: o desenvolvimento profissional docente na Prefeitura Municipal de Piracicaba - Campos, Renan Romero de (Universidade Federal de São Carlos, 2022)
The work proposes to understand how the Career Plan for the Public Magisterium in the Municipality of Piracicaba is being established. This is an instrument of the Human Resources Administration, foreseen by the Brazilian educational legislation for teaching categories, especially for Basic Education. The objective is to understand the specificities of the elaboration of a Career Plan for Public Teaching in the Municipality of Piracicaba, through the analysis of the compatibility of incentives for professional development, in a career, with the organizational objectives of the City Hall. The study focuses on a literature review on the topic of strategic management of people in the public sector, the study of positions and careers, and also the concept of teacher professional development. The Systematic Bibliographic Review focused on career planning in public education was used to map the field of study. As qualitative and quantitative descriptive research strategies, data triangulation is built around 1) Participant Observation, through the political-institutional context of the Municipality of Piracicaba and the Municipal Department of Education aligned with the researcher's experience as a natural member of the Network Municipal Education; 2) Documentary Analysis that breaks down Complementary Law Projects nº 11/2004 and nº 17/2017, which deal with the legislative matter object of this study, in Piracicaba, and were both rejected and archived; and 3) the application of a Survey, through a questionnaire proposed to the target audience of Piracicaban teachers, whose results show an average profile of municipal teachers. From the triangulation of data between Participant Observation, Document Analysis and Survey it led to the conclusion that the City Hall offered career plans consistent with the professional development of teachers, valuing career progression based on academic title, length of service, functional performance and continuing education courses for professional improvement and qualification. The plans, however, have yet to be approved and implemented. The City Hall's objectives, in this sense, consist of complying with current educational legislation, consolidating the structure of the Municipal Education Network and valuing teaching professionals. At the end, possibilities for future studies are proposed related to the teacher's participation in the elaboration of these plans, the legal forecast of career plans for other servants of Basic Education, and the possibilities of access to school management positions.
Municipal public teaching career plan: the professional development of teachers in the Municipality of Piracicaba
Keywords: Educação básica; Gestão de pessoas; Plano de carreira; Magistério público; Basic education; People management; Career path; Public teaching; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA